The relationship of human resource management practices towards organizational commitment in DHL Asia Pacific Shared Services Sdn. Bhd. - Norazila, Othman (2018)
The purpose of this study is to determine the relationship between of Organizational Commitment and Human Resource Management Pradtices among employees at DHL Asia Pacific Shared Services Sdn Bhd. Data were collected from employees. Questionnaires were used and analysed using Statistical Package for Social Science (SPSS) version 21. Using correlation analysis, it was found that there was a significant relationship between the independent variables, namely compensation, performance appraisal and training and development with the dependent variable, organizational commitment. Among the independent variables, performance appraisal was found to be the factor which influenced most significantly relationship with organizational commitment in DHL Asia Pacific Shared Services Sdn Bhd.